The risk of adverse pregnancy outcomes in women who are overweight or obese - Willson Kristyn J; Rumbold Alice R; Athukorala Chaturica; Crowther Caroline A (BMC, 2010)
Abstract Background The prevalence of obesity amongst women bearing children in Australia is rising and has important implications for obstetric care. The aim of this study was to assess the prevalence and impact of mothers being overweight and obese in early to mid-pregnancy on maternal, peripartum and neonatal outcomes. Methods A secondary analysis was performed on data collected from nulliparous women with a singleton pregnancy enrolled in the Australian Collaborative Trial of Supplements with antioxidants Vitamin C and Vitamin E to pregnant women for the prevention of pre-eclampsia (ACTS). Women were categorized into three groups according to their body mass index (BMI): normal (BMI 18.5-24.9 kg/m2); overweight (BMI 25-29.9 kg/m2) and; obese (BMI 30-34.9 kg/m2). Obstetric and perinatal outcomes were compared by univariate and multivariate analyses. Results Of the 1661 women included, 43% were overweight or obese. Obese women were at increased risk of pre-eclampsia (relative risk (RR) 2.99 [95% confidence intervals (CI) 1.88, 4.73], p < 0.0001) and gestational diabetes (RR 2.10 [95%CI 1.17, 3.79], p = 0.01) compared with women with a normal BMI. Obese and overweight women were more likely to be induced and require a caesarean section compared with women of normal BMI (induction - RR 1.33 [95%CI 1.13, 1.57], p = 0.001 and 1.78 [95%CI 1.51, 2.09], p < 0.0001, caesarean section - RR 1.42 [95%CI 1.18, 1.70], p = 0.0002 and 1.63 [95%CI 1.34, 1.99], p < 0.0001). Babies of women who were obese were more likely to be large for gestational age (LFGA) (RR 2.08 [95%CI 1.47, 2.93], p < 0.0001) and macrosomic (RR 4.54 [95%CI 2.01, 10.24], p = 0.0003) compared with those of women with a normal BMI. Conclusion The rate of overweight and obesity is increasing amongst the Australian obstetric population. Women who are overweight and obese have an increased risk of adverse pregnancy outcomes. In particular, obese women are at increased risk of gestational diabetes, pregnancy induced hypertension and pre-eclampsia. Effective preventative strategies are urgently needed. Trial Registration Current Controlled Trials ISRCTN00416244